2021
DOI: 10.1097/aln.0000000000004015
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anesthesia with Targeted Sedation based on Bispectral Index Values Compared with General Anesthesia with Masked Bispectral Index Values to Reduce Delirium: The SHARP Randomized Controlled Trial

Abstract: Background Reducing depth of anesthesia and anesthetic exposure may help prevent delirium, but trials have been conflicting. Most studies were conducted under general anesthesia or in cognitively impaired patients. It is unclear whether reducing depth of anesthesia beyond levels consistent with general anesthesia reduces delirium in cognitively intact patients. The authors’ objective was to determine whether a bundled approach to reduce anesthetic agent exposure as determined by Bispectral In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…In contrast, SA uses a small number of anesthetics and injects anesthesia into the spinal canal space to block neurons. For this reason, the degree of damage to the cognitive function of the patient is low, and the postoperative cognitive function of the patient can be improved [ 21 , 32 , 33 ]. Finally, this work compared the differences in the probability of postoperative respiratory events among patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SA uses a small number of anesthetics and injects anesthesia into the spinal canal space to block neurons. For this reason, the degree of damage to the cognitive function of the patient is low, and the postoperative cognitive function of the patient can be improved [ 21 , 32 , 33 ]. Finally, this work compared the differences in the probability of postoperative respiratory events among patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The adjusted hazard ratio associated with a 1-mmHg increase in time-weighted average of mean arterial pressure less than 65 mmHg was 1.11 (95% CI, 1.03 to 1.20). 2 The study by Brown et al 1 found that the lowest mean arterial pressure was similar in both groups (general anesthesia, 59 [51 to 64] vs . spinal anesthesia, 60 [52 to 64]); however, the relationship between intraoperative hypotension and the subsequent development of delirium might be more of a cumulative exposure response than a single threshold.…”
Section: To the Editormentioning
confidence: 95%
“…Brown et al 1 nicely described their work comparing spinal anesthesia with targeted sedation based on Bispectral Index values compared with general anesthesia (masked Bispectral Index) and the outcome of delirium. Intraoperative hypotension has been associated with delirium.…”
Section: To the Editormentioning
confidence: 99%
“…We read with great interest the recent article by Brown et al 1 regarding the impact of Bispectral Index (BIS)–guided sedation on the incidence of postoperative delirium during spinal anesthesia for spine surgery compared with BIS-masked general anesthesia. We appreciated the originality and efforts of the authors to clarify a still controversial topic such as the connection between depth of the hypnotic component of anesthesia and postoperative delirium.…”
Section: To the Editormentioning
confidence: 99%